2020
DOI: 10.3390/ijgi9070461
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation of Urban Heat Islands for Implementing Nature-Based Solutions: A Case Study of Kurunegala, Sri Lanka

Abstract: Changes in the urban landscape resulting from rapid urbanisation and climate change have the potential to increase land surface temperature (LST) and the incidence of the urban heat island (UHI). An increase in urban heat directly affects urban livelihoods and systems. This study investigated the spatiotemporal variation of the UHI in the Kurunegala urban area (KUA) of North-Western Province, Sri Lanka. The KUA is one of the most intensively developing economic and administrative capitals in Sri Lanka with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 55 publications
(100 reference statements)
3
23
0
Order By: Relevance
“…Historical data linked with population dynamics permits the analysis of interrelationships among urban expansion and the social impacts. Additionally, better spatial resolution data available, like the Sentinel-2 [89], allow the characterization of the urban fabric and its association with the increase of urban artificial impervious surface with the higher patterns of surface urban heat island [90,91].…”
Section: Discussionmentioning
confidence: 99%
“…Historical data linked with population dynamics permits the analysis of interrelationships among urban expansion and the social impacts. Additionally, better spatial resolution data available, like the Sentinel-2 [89], allow the characterization of the urban fabric and its association with the increase of urban artificial impervious surface with the higher patterns of surface urban heat island [90,91].…”
Section: Discussionmentioning
confidence: 99%
“…There are several organizations involved with heat stress, but individual responsibilities are unclear. It is necessary to do physical and quantitative research on heat waves [40,41]. Based on the quantitative research, it needs to define the impact and damage status of heat stress and design databases for continuous data collection and dissemination of information to manage this factor.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the context of India, it seems that for different states, the rainfall trend can be identified as both positive and negative [15][16][17][18][19]. In addition, some studies have shown that urban temperature is rising in Sri Lanka [20]. Analysis of rainfall trends has become a research field that has attracted great interest and enthusiasm in recent times [21].…”
Section: Introductionmentioning
confidence: 99%